2014
DOI: 10.1037/a0033677
|View full text |Cite
|
Sign up to set email alerts
|

I want to help you, but I am not sure why: Gaze-cuing induces altruistic giving.

Abstract: Detecting subtle indicators of trustworthiness is highly adaptive for moving effectively amongst social partners. One powerful signal is gaze direction, which individuals can use to inform (or deceive) by looking toward (or away from) important objects or events in the environment. Here, across 5 experiments, we investigate whether implicit learning about gaze cues can influence subsequent economic transactions; we also examine some of the underlying mechanisms. In the 1st experiment, we demonstrate that peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
35
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 53 publications
(99 reference statements)
7
35
0
3
Order By: Relevance
“…However, subtle behaviours that can be used to deceive others, such as gaze shifts, could have quite specific effects on trust. For example, whether to invest money with another person is influenced by incidental learning of patterns of gaze shifts, as is the decision to be altruistic while computing the likelihood that such an act will be reciprocated in the future INCIDENTAL LEARNING OF TRUST 6 (Rogers, Bayliss et al, 2014). Such decisions might not be affected by general feelings of liking, for example we may trust a lawyer to do their utmost to preserve our freedom, but we may not like them on a personal level; the two feelings are distinct, and can be separated.…”
Section: Incidental Learning Of Trustmentioning
confidence: 99%
“…However, subtle behaviours that can be used to deceive others, such as gaze shifts, could have quite specific effects on trust. For example, whether to invest money with another person is influenced by incidental learning of patterns of gaze shifts, as is the decision to be altruistic while computing the likelihood that such an act will be reciprocated in the future INCIDENTAL LEARNING OF TRUST 6 (Rogers, Bayliss et al, 2014). Such decisions might not be affected by general feelings of liking, for example we may trust a lawyer to do their utmost to preserve our freedom, but we may not like them on a personal level; the two feelings are distinct, and can be separated.…”
Section: Incidental Learning Of Trustmentioning
confidence: 99%
“…At the end of the trial, participants saw a screen saying Please Relax for 1000 ms. A 500 ms stimulus onset asynchrony (SOA) between gaze-cue and target object was used to ensure that it was long enough for gaze to be most strongly encoded and produce measurable ERPs but at the same time short enough to reflexively cue attention (Friesen & Kingstone, 1998 ). This SOA has also been used in all other studies of identity-contingent gaze-cueing and trust (Bayliss et al, 2009 ; Bayliss & Tipper, 2006 ; Rogers et al, 2014 ), facilitating comparison. We did not vary SOA, as this would not allow for a sufficient number of ERP trials to be calculated in the trial period when the gaze-shift occurred.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…For all ERP analyses, we collapsed across the factor of face gender, as this was not of primary interest to our hypotheses and also to retain a sufficient number of trials in the analysis. Trials with errors or reaction times exceeding 1500 ms or two standard deviations above or below each participants mean ( M = 4.6%, SD = 1.5) were removed from the reaction time analyses (in accordance with Bayliss et al ( 2009 ), Bayliss and Tipper ( 2006 ), and Rogers et al ( 2014 )).…”
Section: Design and Proceduresmentioning
confidence: 99%
“…Affective learning can be seen in the way that facial cues shape our lasting impressions of others. In gaze cueing experiments, for example, participants view faces which incidentally gaze to the left or right (e.g., Bayliss, Griffiths, & Tipper, 2009;Bayliss & Tipper, 2006;Rogers et al, 2014). The gaze direction of the face may match or mismatch with the location of a simultaneously appearing target, which the participant is tasked with rapidly identifying.…”
mentioning
confidence: 99%
“…Importantly, the faces in these experiments gaze in a manner that is consistently helpful or unhelpful. The participants later rate faces that gazed unhelpfully as being less trustworthy than those who were helpful (Bayliss & Tipper, 2006;Bayliss et al, 2009), and show less willingness to financially invest in them (Rogers et al, 2014). Subsequent work has demonstrated that emotional reactions during gaze cueing (as measured via facial electromyography) mediate this learning of trust (Manssuer, Pawling, Hayes, & Tipper, 2015).…”
mentioning
confidence: 99%